The impact of IT-technological innovation on the productivity of a bank's employee - Asare Yaw Obeng; Emmanuel Boachie (Cogent Business & Management, 2018)
Banks discretionary devise technology-driven core strategies to leverage trends in information technology to pursue technological innovation in order to improve the productivity of employees. Employee productivity is a considerable unit of measure of a firm's performance and a source of sustaining competition. A logistic regression analysis was conducted using dependent variables of employee_productivity, innovation_impact and innovation_satisfaction, and 12 predictors. The highest positive effect of innovation was on process (improved 39 times more than other predictors), newOrimproved_process was more likely to contribute the highest (34.9) to innovation_satisfaction, and high innovation_impact factor was more likely to contribute the highest (28.7) to employee_productivity among the banks. Exploring and understanding the interrelationships and effects among these variables can provide managers with more reliable and actionable insights to embark on innovation activities that would improve the competence, operational efficiency, productivity of employees, and ultimately their performance.
Keywords: 650